Multiobjective optimization of the semi-open impeller in a centrifugal pump by a multilevel method. - Papierski, Adam; Błaszczyk, Andrzej (Polskie Towarzystwo Mechaniki Teoretycznej i Stosowanej, 2011)
The complete optimization task for the case of the semi-open impeller with straight blades requires description of its geometry by means of, at least, eighteen design variables. In the case of constant meridional cross-section, required are at least eight design variables. Solution of the task with such a great vector of design variables requires much more time. One of the ways to obtain solutions with great variety of design variables is a comprehensive approach to the task including on the partition into minor subtasks. After decomposing the optimization task, one should choose a procedure for solving it. One of such procedures is parametric optimization, which is a two-stage minimization (maximization) method. This optimization is carried out in two levels. On the lower level, the multi-optimization of the decomposed parts of the tasks, depending on design variables, is being held. The solution of the lower level is used in the upper level (coordinating level) to find optimal coordination variables. It has been shown that the result of multi-level optimization and the whole task optimization is the same in limits of accepted accuracy of calculation of the objective functions. Time of the calculation for the multilevel optimization task is over four times shorter than the time of the undecomposed task.

Pełne zadanie optymalizacyjne dla przypadku półotwartego wirnika wymaga z łopatkami o pojedynczej krzywiźnie wymaga opisania jego geometrii za pomocą co najmniej 18 zmiennymi decyzyjnymi, a w przypadku niezmiennego przekroju merydionalnego potrzeba co najmniej 8 zmiennych decyzyjnych. Czas rozwiązania zadania o tak wielkim wymiarze wektora zmiennych decyzyjnych jest bardzo duży. Jednym ze sposobów rozwiązania zadań z dużą ilością zmiennych decyzyjnych jest systemowe podejście do zagadnienia polegające na podziale problemu na mniejsze części. Po zdekomponowaniu problemu optymalizacyjnego należy wybrać metodę rozwiązania zadania. Jedną z takich metod jest metoda optymalizacji parametrycznej, która jest dwuetapową metodą minimalizacji (maksymalizacji). Optymalizacja ta polega na tym, że dokonujemy jej na dwóch poziomach. Na poziomie dolnym przeprowadza się wielokrotną optymalizację zdekomponowanych części problemu względem ich zmiennych decyzyjnych. Wynik optymalizacji na poziomie dolnym jest wykorzystywany na poziomie górnym, zwanym koordynacyjnym, do znajdowania optymalnych wartości zmiennych koordynacyjnych. Wykazano, że wynik optymalizacji wielopoziomowej i pełnego zadania optymalizacji jest taki sam w granicach przyjętej dokładności obliczeń funkcji celu. Czas obliczeń zadania optymalizacji wielopoziomowej jest ponad czterokrotnie mniejszy niż zadania niezdekompowanego.
Wielokryterialna optymalizacja półotwartego wirnika odśrodkowej pompy metodą wielopoziomową.
Keywords: semi-open impeller; multilevel optimization; centrifugal pump; półotwarty wirnik; wielopoziomowa optymalizacja; metoda optymalizacji parametrycznej; optymalizacja; zdekomponowanie problemu